How India Voted: The use of social media - Pal, Joyojeet; Meena, Azhagu; Charles, Drupa Dinnie; Panda, Anmol (Seminar, 2019)
Much has been said about politicians and what they have talked about on social media. Cambridge Analytica made election manipulation an international sport, while Donald Trump elevated ‘Fake News’ to verboten status in the mainstream media, the very target of his attacks. The corresponding promotion of social media to the preferred line of output for political actors has highlighted one significant change in political communications in this generation – politicians want to carefully manage the discourse in terms of what they talk about, when, and how. Narendra Modi mastered this style of output in the run up to the 2014 election when he more or less stopped all interaction with professional journalists and moved exclusively to communicating on social media.